A model-based fault-detection strategy in DC/AC conversion. Issue 2 (2020) - Pyrkin, A.; Cisneros, R.; Campos-Delgado, D.U.; Bobtsov, A.; Somov, S.
Abstract: An open-circuit fault-detection strategy is here proposed for single-phase DC/AC conversion. The power converter under consideration consists of an H-bridge and a capacitor with parallel resistance and current source in its DC side—these last two stand for the unknown system load and energy injection from renewable resources, respectively. An inductor filter is also included as a coupling element to the AC network. When an open-circuit fault occurs in the H-bridge, the resulting AC output waveform is asymmetric, and induces DC and harmonic components to the network. Hence, by using an additive fault modeling, the fault signature can be expressed by a constant term fdc and a fluctuating signal. The sign of fdc allows to determine the pair of faulty switches in the H-bridge. In this work, an DREM-based identification scheme is proposed to estimate fdc . Through the sign of its estimate, it is possible to detect the pair of faulty switches. To assess our approach, simulation results are included.